Islamic School Students’ Online Proselytizing Skills Enhancement through Graphic Design Learning (Decode: Jurnal Pendidikan Teknologi Informasi, 2024)
Islamic online proselytizing (e-dakwah) is the utilization of digital technology for motivating people to goodness based on Islamic principles, Al Qur’an and As-Sunnah. This study aims to implement a graphic design learning technology to improve students’ skills in e-dakwah, where all Muslims are obliged to carry out this virtue. The educators conducted the learning program at SMK-IT Ibnul Qayyim Islamic School (IQIS) of Makassar. The Analyze, State, Select, Utilize, Require, dan Evaluate (ASSURE) model is adopted to ensure that the learning activity is well-planned, effective, and achieves its objectives. The students' outcomes are expected to understand knowledge of graphic design and be able to create Islamic content using free apps via smartphones. They learned through a combination of lectures, demonstrations, and hands-on activities. Furthermore, the educators evaluate the learning process using multi-assessment techniques such as the pre-test, post-test model, and practical test. For the hands-on practice, the educators present it through a graphic design competition. The assessment instruments are designed based on lower-order thinking skills (LOTS) and higher-order thinking skills (HOTS) levels in Bloom's revised taxonomy. The research findings indicate a significant improvement in the students' skills quality. This achievement is expected to inspire students' creativity, prepare them to become Muslims with the spirit of inviting goodness, and limit unnecessary smartphone activities.